Characterization of a Nitrilase and a Nitrile Hydratase from Pseudomonas sp. Strain UW4 That Converts Indole-3-Acetonitrile to Indole-3-Acetic Acid - Duca, Daiana; Rose, David R.; Glick, Bernard R. (Applied and environmental microbiology, 2014)
Indole-3-acetic acid (IAA) is a fundamental phytohormone with the ability to control many aspects of plant growth and development. Pseudomonas sp. strain UW4 is a rhizospheric plant growth-promoting bacterium that produces and secretes IAA. While several putative IAA biosynthetic genes have been reported in this bacterium, the pathways leading to the production of IAA in strain UW4 are unclear. Here, the presence of the indole-3-acetamide (IAM) and indole-3-acetaldoxime/indole-3-acetonitrile (IAOx/IAN) pathways of IAA biosynthesis is described, and the specific role of two of the enzymes (nitrilase and nitrile hydratase) that mediate these pathways is assessed. The genes encoding these two enzymes were expressed in Escherichia coli , and the enzymes were isolated and characterized. Substrate-feeding assays indicate that the nitrilase produces both IAM and IAA from the IAN substrate, while the nitrile hydratase only produces IAM. The two nitrile-hydrolyzing enzymes have very different temperature and pH optimums. Nitrilase prefers a temperature of 50°C and a pH of 6, while nitrile hydratase prefers 4°C and a pH of 7.5. Based on multiple sequence alignments and motif analyses, physicochemical properties and enzyme assays, it is concluded that the UW4 nitrilase has an aromatic substrate specificity. The nitrile hydratase is identified as an iron-type metalloenzyme that does not require the help of a P47K activator protein to be active. These data are interpreted in terms of a preliminary model for the biosynthesis of IAA in this bacterium.